MOLECULAR MAPPING OF BPH RESISTANT GENE(S) IN RICE (Oryza sativa L.) - CH.V. DURGARANI, A. MALIHA, M. BALRAM, N. RAMA GOPALA VARMA and (The Journal of Research, PJTSAU, 2017)
Rice cultivation covers 9% of world’s total arable land of which 89% accounts from Asia (IRRI). India has largest area (43.86 million hectares) under rice with a production of 152.6 million tonnes, next to China (FAO 2013-14). In Telangana rice is cultivated in an area of 16.73 lakh hectares, with a production of 44.8 lakh tonnes. Approximately 52% of the global rice production is lost annually owing to the damage caused by biotic stress factors of which 25% is attributed to the attack by insect pests (Yarasi et al., 2008).